(untitled) (Archivo Agustiniano, 2022)
This article contains a thorough study of a complete inventory of the Santo Niño de Cebu convent drawn up in 1735 by the Augustinian prior Juan de Albarrán.The inventory offers very interesting information regarding the agrarian properties, the urban properties of the city of Cebu and the chaplaincies managed by the Augustinians of Santo Niño.Additionally, the inventory provides information on the origins and development of the convent, with abundant references to the society of that time. Finally, this study portrays an analysis of the historical evolution of the Santo Niño de Cebu convent in its first one hundred and seventy-five years of existence.